Jarak Genetik Udang Galah Dari Muara Sungai Barito, Kintap dan Pagatan Sebagai Calon Induk Unggul - Yulius Kisworo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
This study aims to gain an overview of genetic distances based on the characterization of The Giant Freshwater Prawn, with survey research methods. The results of the analysis of genetic distances showed Barito River broodstock have different characteristics with broodstock Kintap and Pagatan. Broodstock Kintap and Pagatan still have similar characteristics.